Layered in-situ stress measurement method for perforated interval of Nanpu Gas Storage, Jidong Oilfield - Yuehui YANG; Guangliang GAO; Fang WANG; Chaofeng LI; Wenjin WAN; Dongsheng SUN; Qunce CHEN (You-qi chuyun, 2022)
In-situ stress is an important basic data for determining the top and bottom limit of operating pressure of underground gas storage, evaluating the stability of geological body and analyzing the fault activity in the storage area. Herein, the layered in-situ stress measurement method, test equipment and construction process of perforated interval were briefly introduced, and the minimum principal stresses of 2 reservoir sections and 3 mudstone caprock sections in the depth range of 4 150.0 m to 4 338.0 m of Well NP36-X in Pugu-2 Block of Jidong Oilfield were measured with this method. As shown by the results, the tests were repeated over 3 times for each section, and the fracture shut-in pressure in multiple tests had good consistency with the relative error less than 5%. Besides, the minimum principal stress in the mudstone caprock of Well NP36-X was determined to be 72.40 MPa to 74.27 MPa with various fracture shut-in pressure analysis methods. Moreover, the minimum principal stress of high permeability formation was comprehensively determined to be 54.89 MPa to 60.25 MPa with the fracture extension pressure and the injection flow. As an exploration based on the in-situ stress measurement method for the perforated interval of old wells, this method, especially the field application test based on the fracture extension pressure and the injection flow, can partly compensate the insufficiency that the classical in-situ stress measurement method of hydraulic fracturing is not applicable to the high permeability formation.